Identification of Saline Groundwater and the Hydrogeochemistry in Highland of Ba’kelalan Region Using Geophysical and Chemical Methods - Ongetta, Stephan (Curtin University, 2020)
The communities at Ba’kelalan of Sarawak have been using saline groundwater for commercial salt production. The study infers that there is an increase in salinity of groundwater with respect to season affecting the amount of salt production. Based on the results of the geochemical and geophysical studies, the source of the existing well water is mainly due to the dissolution of brine and they are connected through a fault system reaching the shallow levels.